2016
DOI: 10.1111/jscm.12101
|View full text |Cite
|
Sign up to set email alerts
|

Supply Chain Psychological Contract Breach: An Experimental Study across National Cultures

Abstract: Supply disruptions are commonplace in today's global supply chain environment. The sheer magnitude of daily transactions makes it inevitable that there will be disruptions, further exacerbated by differences in cultural norms and attitudes that add a layer of complexity to managerial response. In this research, we examine the impact of national culture on individuals' responses to supply disruptions due to psychological contract breach. Using data from controlled experiments conducted with 158 subjects in Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 69 publications
1
48
0
Order By: Relevance
“…This finding suggests that cognitive processes are crucial microfoundations for explaining heterogeneity in organization‐level supply chain disruption management, thus adding empirical evidence to a growing stream of literature on managerial cognition in the general management (Helfat & Peteraf, ; Maitland & Sammartino, ) and SCM literature (Kaufmann et al., ; Stanczyk et al., ). Our research on the cognitive microfoundations of responses to supplier‐induced disruptions complements prior studies that investigate the social and psychological implications of supply chain disruptions, such as perceptions of justice (e.g., Wang et al., ) and psychological contract breaches (e.g., Eckerd et al., ).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…This finding suggests that cognitive processes are crucial microfoundations for explaining heterogeneity in organization‐level supply chain disruption management, thus adding empirical evidence to a growing stream of literature on managerial cognition in the general management (Helfat & Peteraf, ; Maitland & Sammartino, ) and SCM literature (Kaufmann et al., ; Stanczyk et al., ). Our research on the cognitive microfoundations of responses to supplier‐induced disruptions complements prior studies that investigate the social and psychological implications of supply chain disruptions, such as perceptions of justice (e.g., Wang et al., ) and psychological contract breaches (e.g., Eckerd et al., ).…”
Section: Discussionmentioning
confidence: 63%
“…A separate stream of literature on supply chain disruptions has explored the strategies for preemptively reducing disruption risks (Kleindorfer & Saad, ; Speier, Whipple, Closs & Voss, ; Zsidisin & Smith, ), the capabilities to recover from supply chain disruptions (Blackhurst, Dunn & Craighead, ; Craighead et al., ), and the performance effects of supply chain disruptions (Hendricks & Singhal, ,b). Furthermore, researchers have recently begun to explore the role of individual‐level factors in responses to supply chain disruptions, such as psychological contract breaches (Eckerd, Boyer, Qi, Eckerd & Hill, ; Eckerd, Hill, Boyer, Donohue & Ward, ) or perceptions of justice (Wang et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Their results revealed that contractual governance is more suitable for individualistic and low uncertainty avoidance cultures, whereas relational governance is more suitable for collectivist and high uncertainty avoidance societies. Eckerd et al (2016) examined the behaviors of US and Chinese buyers following a post-psychological contract breach, which is "when an individual perceives insufficient fulfillment of obligations believed due from the contract partner" (p. 69).…”
Section: Governance Mechanismsmentioning
confidence: 99%
“…The questionnaire's first items served as a manipulation check, inquiring about the participant's perception of the counterpart's honesty (a = .89) and of the counterpart's ethicality (adapted from Pelletier & Bligh, 2006; a = .90). To assess H2 through H5, subsequent items then asked participants whether they were angry with their counterpart and with themselves (adapted from Gelbrich, 2010;Johnson, Matear & Thomson, 2011; a = .94 and a = .89 respectively), and how willing they were to negotiate with their counterpart in the future (adapted from Eckerd, Boyer, Qi, Eckerd & Hill, 2016). All items used 7-point Likert-type scales.…”
Section: Study 4: Consequences Of Bluffing and Lying For The Targetmentioning
confidence: 99%